A polylysine conductive hydrogel with both ROS scavenging and multi-antibacterial properties
By constructing a polylysine conductive hydrogel with multiple crosslinking networks, the problems of bacterial resistance and ROS impact on tissue regeneration are solved, and efficient ROS removal and multiple antibacterial properties are achieved, which are suitable for trauma repair and tissue engineering in the field of biomedical science.
Patent Information
- Application Number
- CN202210483337.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-06
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-05-06
AI Technical Summary
The prior art is difficult to effectively solve the effect of bacterial resistance and overexpressed ROS in the tissue microenvironment on tissue regeneration and repair.
By constructing a polylysine conductive hydrogel with multiple crosslinking networks, ROS clearance and multiple antibacterial properties are achieved using the chemical crosslinking reaction of Schiff base and the near-infrared light response of the photoinitiator.
The hydrogel has excellent mechanical strength, antibacterial properties and ROS clearance under physiological conditions, and is suitable for trauma repair, cardiovascular and tissue engineering and other fields.
Smart Images

Figure CN114805854B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedical polymer materials and medical devices, and specifically relates to a polylysine conductive hydrogel with ROS scavenging and multiple antibacterial properties. Background Art
[0002] Bacterial infection is one of the diseases that seriously affect human life, health and safety. More than 10 million patients worldwide are suffering from bacterial invasion every year. Since the mass production of penicillin in 1940, penicillin, as the nemesis of bacterial diseases, has opened up a new way for the treatment of clinically related diseases and saved countless patients. However, the increase in bacterial resistance caused by the abuse of antibiotics due to excessive or improper use of antibiotics has seriously affected the efficiency of antibiotic use, resulting in waste of medical resources and high clinical mortality. Therefore, it is urgent to develop new sterilization technologies and antibacterial materials to eliminate or slow down the emergence of drug-resistant bacteria. In recent years, with the development of technology, a new generation of antibacterial strategies represented by antibacterial materials has become a potential means to replace traditional antibiotic therapy. Compared with a single method, the antibacterial strategy that combines multiple sterilization methods is more effective, has higher sterilization efficiency, and will not or rarely produce drug-resistant bacteria.
[0003] During the process of tissue repair and regeneration, the overexpression of ROS in the corresponding tissue microenvironment seriously affects the regeneration and remodeling of damaged tissues, causing disturbances in the physiological environment of tissues, and thus leading to the occurrence of inflammatory diseases. Therefore, timely and effective elimination of overexpressed ROS in damaged tissues is of great significance for improving the inflammatory level of the tissue microenvironment and promoting the regeneration and repair of tissues. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a polylysine conductive hydrogel with both ROS scavenging and multiple antibacterial properties. The invention aims to construct a hydrogel with a multiple cross-linked network through the action of Schiff base and chemical cross-linking agent, and endow it with excellent mechanical strength, multiple antibacterial properties, tissue compatibility, ROS scavenging ability and electrical conduction. The implementation conditions are mild and controllable, and the performance is adjustable. It can be widely used in biomedical fields such as wound repair, cardiovascular, wearable devices and tissue engineering.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] (1) sequentially adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide to an L-arginine hydrochloride solution to activate the carboxyl group of the L-arginine hydrochloride, and then adding polylysine to react, dialyzing and purifying after the reaction is completed, and then freeze-drying to obtain an L-arginine-modified polylysine polymer;
[0007] (2) adding a sodium periodate solution to a mucopolysaccharide solution containing a vicinal diol structure in a dark room and reacting the solution, adding ethylene glycol after the reaction is completed to terminate the continued oxidation of the mucopolysaccharide structure by sodium periodate, and then dialysis purification, and freeze-drying to obtain a natural mucopolysaccharide functionalized with aldehyde groups;
[0008] (3) The L-arginine-modified polylysine polymer, the aldehyde-functionalized natural mucopolysaccharide, the chemical crosslinking agent, the near-infrared light-responsive nanocomposite material and the photoinitiator are dissolved and mixed in sequence, and then cured by ultraviolet light to obtain the polylysine conductive hydrogel.
[0009] Preferably, the concentration of the polylysine solution in step (1) is 1-30 mg / mL, and the molecular weight of polylysine is 2000-5000 Da; the molar ratio of the carboxyl group of L-arginine hydrochloride to the amino group of polylysine is 5:1-1:2; the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to L-arginine hydrochloride is 2:1-1:3; the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 3:1-1:1; the reaction temperature is 4-60°C, and the reaction time is 12-72 hours; the dialysis temperature is 25-60°C, the dialysis bag cutoff size is 500-3000 Da, and the dialysis time is 12-96 hours.
[0010] Preferably, the concentration of the sodium periodate solution in step (2) is 10-200 mg / mL, the addition time of the sodium periodate solution is 10-60 minutes, the reaction time after the addition of the sodium periodate solution is 1-3 hours, the reaction time after the addition of ethylene glycol is 0.5-3 hours, the reaction temperature is 25-60°C, the dialysis temperature is 25-60°C, the dialysis bag cutoff size is 1000-12000Da, and the dialysis time is 12-96 hours.
[0011] Preferably, the mucopolysaccharide in step (2) includes but is not limited to at least one of sodium hyaluronate, sodium alginate, and sodium carboxymethyl cellulose; the concentration of the mucopolysaccharide is 1-10 mg / mL, the dissolution temperature is 25-60° C., and the dissolution time is 3-36 hours.
[0012] Preferably, the concentration of the polylysine polymer modified with polylysine L-arginine in step (3) is 50-200 mg / mL, the concentration of the natural mucopolysaccharide modified with aldehyde functionalization is 10-100 mg / mL, the concentration of the chemical crosslinking agent is 30-150 mg / mL, the concentration of the near-infrared light-responsive nanocomposite material is 1-5 mg / mL, the concentration of the photoinitiator is 0.5-20 mg / mL, and the illumination time is 0-90 minutes.
[0013] Preferably, the chemical cross-linking agent in step (3) includes but is not limited to at least one of N,N′-methylenebisacrylamide, polyethylene glycol diacrylate, and polyether diacrylate.
[0014] Preferably, the near-infrared light-responsive nanocomposite material described in step (3) includes but is not limited to at least one of carbon nanotubes, graphene, and ferrosoferric oxide nanoparticles.
[0015] Preferably, the photoinitiator described in step (3) includes but is not limited to at least one of I2959, LAP, and α-ketoglutaric acid.
[0016] The invention also provides a polylysine conductive hydrogel prepared by the method.
[0017] The present invention also provides applications of the polylysine conductive hydrogel prepared by the above method in biomedical fields such as wound repair, cardiovascular, wearable devices and tissue engineering.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The present invention utilizes L-arginine hydrochloride to functionally modify natural antibacterial materials and then mixes them with aldehyde-functionalized mucopolysaccharide materials. Under physiological conditions, a chemical crosslinking reaction of Schiff base occurs to construct an endogenous broad-spectrum antibacterial hydrogel scaffold, which is used to simulate the dynamic microenvironment of the extracellular matrix and realize its function of promoting tissue repair and reconstruction. In addition, by introducing a chemical crosslinking agent, the hydrogel forms a multiple crosslinked network under ultraviolet light irradiation, and the mechanical strength of the polylysine hydrogel is further improved by the strong and weak combination formed by the dynamic crosslinking of Schiff base and the covalent crosslinking of carbon-carbon double bonds, ensuring that the matrix will not collapse while the hydrogel scaffold exerts its physiological functions. Finally, by loading a nanocomposite material with near-infrared light response, the hydrogel scaffold is endowed with dual antibacterial efficacy under near-infrared irradiation, and its good electrical conductivity is achieved. The polylysine hydrogel gelation method of the present invention is mild and environmentally friendly, no by-products are generated, the implementation conditions are mild and controllable, and the performance is adjustable. In addition, due to the presence of polylysine and L-arginine, the hydrogel has good tissue compatibility and ROS scavenging ability, and can be widely used in biomedical fields such as wound repair, cardiovascular, wearable devices and tissue engineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 1 is a diagram showing the synthesis mechanism of the L-arginine-modified polylysine polymer of the present invention.
[0021] Figure 2 It is the hydrogen nuclear magnetic resonance spectrum of the L-arginine-modified polylysine polymer of the present invention.
[0022] Figure 3It is a schematic diagram of the conductive properties of the polylysine conductive hydrogel of the present invention.
[0023] Figure 4 Schematic diagram of the antibacterial effect of the polylysine conductive hydrogel of the present invention.
[0024] Figure 5 Schematic diagram of thermal imaging of the polymerizable lysine conductive hydrogel of the present invention.
[0025] Figure 6 It is a schematic diagram of DPPH removal of the polylysine conductive hydrogel of the present invention.
[0026] Figure 7 This is a graph showing the antioxidant data of the polylysine conductive hydrogel of the present invention.
[0027] Figure 8 Schematic diagram of the polymerizable lysine conductive hydrogel of the present invention for removing active oxygen.
[0028] Fig. 9 A scanning electron microscope schematic diagram of the polymerizable lysine conductive hydrogel of the present invention. DETAILED DESCRIPTION
[0029] According to the following examples and drawings, the present invention can be better understood and further described. However, the contents described in the examples are only used to illustrate the present invention, rather than to limit the claims of the present invention.
[0030] Example 1
[0031] (1) 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are sequentially added to an L-arginine hydrochloride solution to activate the carboxyl group of the L-arginine hydrochloride, and then polylysine is added to react at 30° C. for 12 hours. After the reaction is completed, the reaction solution is transferred to a dialysis bag and dialyzed for 24 hours for purification, and finally freeze-dried using a freeze dryer to obtain an L-arginine-modified polylysine polymer; wherein the polylysine The concentration of the amino acid solution was 10 mg / mL, the molar ratio of the carboxyl group of L-arginine hydrochloride to the amino group of polylysine was 1:1, the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to L-arginine hydrochloride was 1:1, the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide was 1.2:1, the dialysis temperature was 37°C, and the dialysis bag cutoff size was 3000Da.
[0032] (2) First, a 10 mg / mL sodium alginate solution was prepared by stirring at 30°C for 6 hours to dissolve it. Then, a 100 mg / mL sodium periodate solution was added dropwise to the mucopolysaccharide solution containing a vicinal diol structure using a constant pressure titration funnel in a dark room to react for 2.5 hours. Ethylene glycol was added to continue the reaction for 2 hours to terminate the continued oxidation of the mucopolysaccharide structure by sodium periodate. The reaction solution was then transferred to a dialysis bag and dialyzed for 36 hours for purification. The aldehyde functionalized sodium alginate polymer was obtained by freeze drying. The reaction time after adding the sodium periodate solution was 1.5 hours, the reaction temperature was 30°C, the dialysis temperature was 37°C, and the retention capacity of the dialysis bag was 3500Da.
[0033] (3) The L-arginine-modified polylysine polymer (100 mg / mL), aldehyde-functionalized sodium alginate (100 mg / mL), polyethylene glycol diacrylate (40 mg / mL), carbon nanotubes (4 mg / mL) and photoinitiator I2959 (5 mg / mL) were dissolved and mixed evenly, and then irradiated with 365 nm ultraviolet light for 10 minutes to cure, thereby obtaining a polylysine conductive hydrogel.
[0034] Example 2
[0035] (1) 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are sequentially added to an L-arginine hydrochloride solution to activate the carboxyl group of the L-arginine hydrochloride, and then polylysine is added to react at 30° C. for 12 hours. After the reaction is completed, the reaction solution is transferred to a dialysis bag and dialyzed for 24 hours for purification, and finally freeze-dried using a freeze dryer to obtain an L-arginine-modified polylysine polymer; wherein the concentration of the polylysine solution is 20 mg / mL, the molar ratio of the carboxyl group of the L-arginine hydrochloride to the amino group of the polylysine is 1:2, the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to L-arginine hydrochloride is 1:1, and the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 2:1, the dialysis temperature is 30° C., and the dialysis bag cutoff size is 1000 Da. About 5.0 mg of L-arginine-modified polylysine polymer was dissolved in 0.6 mL of D2O and then analyzed by nuclear magnetic resonance spectroscopy. 1 H-NMR characterization, test results Figure 2 shown.
[0036] (2) First, a 10 mg / mL sodium carboxymethyl cellulose solution was prepared by stirring at 30°C for 12 hours to dissolve, and then a 10 mg / mL sodium periodate solution was added dropwise to the mucopolysaccharide solution containing a vicinal diol structure using a constant pressure titration funnel in a dark room for a reaction of 3 hours. Ethylene glycol was added to continue the reaction for 1 hour to terminate the continued oxidation of the mucopolysaccharide structure by sodium periodate, and then the reaction solution was transferred to a dialysis bag and dialyzed for 48 hours for purification. The aldehyde-functionalized sodium carboxymethyl cellulose polymer was obtained by freeze-drying; wherein the reaction time after adding the sodium periodate solution was 0.5 hour, the reaction temperature was 30°C, the dialysis temperature was 30°C, and the retention capacity of the dialysis bag was 3500Da.
[0037] (3) The L-arginine-modified polylysine polymer (200 mg / mL), aldehyde-functionalized sodium carboxymethyl cellulose (50 mg / mL), polyethylene glycol diacrylate (20 mg / mL), carbon nanotubes (1 mg / mL) and photoinitiator I2959 (1 mg / mL) were dissolved and mixed evenly, and then irradiated with 365 nm ultraviolet light for 5 minutes to cure, thereby obtaining a polylysine conductive hydrogel.
[0038] Example 3
[0039] (1) 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are sequentially added to an L-arginine hydrochloride solution to activate the carboxyl group of the L-arginine hydrochloride, and then polylysine is added to react at 30° C. for 12 hours. After the reaction is completed, the reaction solution is transferred to a dialysis bag and dialyzed for 24 hours for purification, and finally freeze-dried using a freeze dryer to obtain an L-arginine-modified polylysine polymer; wherein the concentration of the polylysine solution is 15 mg / mL, the molar ratio of the carboxyl group of the L-arginine hydrochloride to the amino group of the polylysine is 2:1, the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to L-arginine hydrochloride is 2:1, the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 2:1, the dialysis temperature is 40° C., and the dialysis bag cutoff size is 1000 Da.
[0040] (2) First, a 5 mg / mL sodium hyaluronate solution was prepared by stirring at 30°C for 24 hours to dissolve. Then, a 20 mg / mL sodium periodate solution was added dropwise to a mucopolysaccharide solution containing a vicinal diol structure using a constant pressure titration funnel in a dark room for a reaction of 4 hours. Ethylene glycol was added to continue the reaction for 2 hours to terminate the continued oxidation of the mucopolysaccharide structure by sodium periodate. The reaction solution was then transferred to a dialysis bag and dialyzed for 48 hours for purification. The aldehyde-functionalized sodium hyaluronate polymer was obtained by freeze drying. The reaction time after adding the sodium periodate solution was 0.5 hours, the reaction temperature was 30°C, the dialysis temperature was 37°C, and the retention capacity of the dialysis bag was 3500Da.
[0041] (3) The L-arginine-modified polylysine polymer (150 mg / mL), aldehyde-functionalized sodium hyaluronate (50 mg / mL), polyether diacrylate (10 mg / mL), carbon nanotubes (1 mg / mL) and photoinitiator I2959 (1 mg / mL) were dissolved and mixed evenly, and then irradiated with 365 nm ultraviolet light for 5 minutes to cure, thereby obtaining a polylysine conductive hydrogel.
[0042] Example 4
[0043] (1) 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are sequentially added to an L-arginine hydrochloride solution to activate the carboxyl group of the L-arginine hydrochloride, and then polylysine is added to react at 30° C. for 24 hours. After the reaction is completed, the reaction solution is transferred to a dialysis bag and dialyzed for 24 hours for purification, and finally freeze-dried using a freeze dryer to obtain an L-arginine-modified polylysine polymer; wherein the concentration of the polylysine solution is 15 mg / mL, the molar ratio of the carboxyl group of the L-arginine hydrochloride to the amino group of the polylysine is 2:1, the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to L-arginine hydrochloride is 2:1, the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 2:1, the dialysis temperature is 40° C., and the dialysis bag cutoff size is 1000 Da.
[0044] (2) First, a 10 mg / mL sodium hyaluronate solution was prepared by stirring at 30°C for 24 hours to dissolve, and then a 20 mg / mL sodium periodate solution was added dropwise to a mucopolysaccharide solution containing a vicinal diol structure using a constant pressure titration funnel in a dark room for 2 hours. Ethylene glycol was added to continue the reaction for 1 hour to terminate the continued oxidation of the mucopolysaccharide structure by sodium periodate, and then the reaction solution was transferred to a dialysis bag and dialyzed for 48 hours for purification. The aldehyde-functionalized sodium hyaluronate polymer was obtained by freeze-drying; wherein the reaction time after adding the sodium periodate solution was 1 hour, the reaction temperature was 37°C, the dialysis temperature was 37°C, and the retention capacity of the dialysis bag was 12000Da.
[0045] (3) The L-arginine-modified polylysine polymer (100 mg / mL), aldehyde-functionalized sodium hyaluronate (100 mg / mL), polyether diacrylate (10 mg / mL), graphene (1 mg / mL) and photoinitiator I2959 (1 mg / mL) were dissolved and mixed evenly, and then irradiated with 365 nm ultraviolet light for 10 minutes to cure, thereby obtaining a polylysine conductive hydrogel.
[0046] (4) The polylysine conductive hydrogel was co-cultured with Staphylococcus aureus and Escherichia coli to evaluate its antibacterial properties, and its thermal conductivity was evaluated using a thermal imaging instrument.
[0047] Example 5
[0048] (1) 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are sequentially added to an L-arginine hydrochloride solution to activate the carboxyl group of the L-arginine hydrochloride, and then polylysine is added to react at 37° C. for 24 hours. After the reaction is completed, the reaction solution is transferred to a dialysis bag and dialyzed for 24 hours for purification, and finally freeze-dried using a freeze dryer to obtain an L-arginine-modified polylysine polymer; wherein the concentration of the polylysine solution is 30 mg / mL, the molar ratio of the carboxyl group of the L-arginine hydrochloride to the amino group of the polylysine is 3:1, the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to L-arginine hydrochloride is 1:1, and the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 1:1, the dialysis temperature is 37° C., and the dialysis bag cutoff size is 500 Da.
[0049] (2) First, a 10 mg / mL sodium hyaluronate solution was prepared by stirring at 50°C for 12 hours to dissolve. Then, a 50 mg / mL sodium periodate solution was added dropwise to the mucopolysaccharide solution containing a vicinal diol structure using a constant pressure titration funnel in a dark room for 2 hours. Ethylene glycol was added to continue the reaction for 2 hours to terminate the continued oxidation of the mucopolysaccharide structure by sodium periodate. The reaction solution was then transferred to a dialysis bag and dialyzed for 96 hours for purification. The aldehyde-functionalized sodium hyaluronate polymer was obtained by freeze drying. The reaction time after adding the sodium periodate solution was 0.5 hours, the reaction temperature was 50°C, the dialysis temperature was 30°C, and the retention capacity of the dialysis bag was 3000Da.
[0050] (3) The L-arginine-modified polylysine polymer (200 mg / mL), aldehyde-functionalized sodium hyaluronate (80 mg / mL), polyethylene glycol diacrylate (50 mg / mL), ferrosoferric oxide nanoparticles (1 mg / mL) and photoinitiator I2959 (1 mg / mL) were dissolved and mixed evenly, and then irradiated with 365 nm ultraviolet light for 20 minutes to cure, thereby obtaining a polylysine conductive hydrogel.
[0051] (4) The poly-lysine conductive hydrogel was subjected to a DPPH scavenging test to evaluate its antioxidant property, and an intracellular ROS scavenging test was performed using H9C2 cells.
[0052] In summary, the present invention provides a method of constructing a polylysine conductive hydrogel with ROS scavenging and multiple antibacterial properties by using a dynamic chemical synergistic crosslinking strategy of light-initiated free radical polymerization and Schiff base, which is used to simulate the dynamic microenvironment of the extracellular matrix and realize its function of promoting tissue repair and reconstruction. The polylysine conductive hydrogel is endowed with dual antibacterial effects through near-infrared beam excitation, and its good electrical conductivity is achieved. In addition, the hydrogel also has good tissue compatibility and ROS scavenging ability, and can be widely used in biomedical fields such as wound repair, cardiovascular, wearable devices, and tissue engineering.
Claims
1. A polylysine conductive hydrogel with both ROS scavenging and multi-antibacterial properties, characterized in that: The following steps are involved: (1) sequentially adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide to an L-arginine hydrochloride solution to activate the carboxyl group of the L-arginine hydrochloride, and then adding polylysine to react, dialyzing and purifying after the reaction is completed, and then freeze-drying to obtain an L-arginine-modified polylysine polymer; (2) in a dark room, a sodium periodate solution is added dropwise to a mucopolysaccharide solution containing a vicinal diol structure to react, and after the reaction is completed, ethylene glycol is added to continue the reaction, followed by dialysis purification, and freeze-drying to obtain a natural mucopolysaccharide functionalized with aldehyde groups; (3) The L-arginine-modified polylysine polymer, the aldehyde-functionalized natural mucopolysaccharide, the chemical crosslinking agent, the near-infrared light-responsive nanocomposite material and the photoinitiator are dissolved and mixed in sequence, and then cured by ultraviolet light to obtain the polylysine conductive hydrogel.
2. The polylysine conductive hydrogel according to claim 1, characterized in that: The concentration of the polylysine solution in step (1) is 1-30 mg / mL, and the molecular weight of polylysine is 2000-5000 Da; the molar ratio of the carboxyl group of L-arginine hydrochloride to the amino group of polylysine is 5:1-1:2; the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to L-arginine hydrochloride is 2:1-1:3; the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 3:1-1:1; the reaction temperature is 4-60°C, and the reaction time is 12-72 hours; the dialysis temperature is 25-60°C, the dialysis bag retention capacity is 500-3000 Da, and the dialysis time is 12-96 hours.
3. The polylysine conductive hydrogel according to claim 1, characterized in that: The concentration of the sodium periodate solution in step (2) is 10-200 mg / mL, the dropping time of the sodium periodate solution is 10-60 minutes, the reaction time after dropping the sodium periodate solution is 1-3 hours, the reaction time after dropping ethylene glycol is 0.5-3 hours, the reaction temperature is 25-60° C., the dialysis temperature is 25-60° C., the dialysis bag cutoff size is 1000-12000 Da, and the dialysis time is 12-96 hours.
4. The polylysine conductive hydrogel according to claim 1, characterized in that: The mucopolysaccharide in step (2) includes at least one of sodium hyaluronate and sodium carboxymethyl cellulose; the concentration of the mucopolysaccharide is 1-10 mg / mL, the dissolution temperature is 25-60° C., and the dissolution time is 3-36 hours.
5. The polylysine conductive hydrogel according to claim 1, characterized in that: The concentration of the L-arginine modified polylysine polymer in step (3) is 50-200 mg / mL, the concentration of the aldehyde functionalized modified natural mucopolysaccharide is 10-100 mg / mL, the concentration of the chemical crosslinking agent is 30-150 mg / mL, the concentration of the near-infrared light responsive nanocomposite material is 1-5 mg / mL, the concentration of the photoinitiator is 0.5-20 mg / mL, and the illumination time is 0-90 minutes.
6. The polylysine conductive hydrogel according to claim 1, characterized in that: The chemical cross-linking agent described in step (3) includes at least one of N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, and polyether diacrylate.
7. The polylysine conductive hydrogel according to claim 1, characterized in that: The near-infrared light-responsive nanocomposite material described in step (3) comprises at least one of carbon nanotubes, graphene, and ferrosoferric oxide nanoparticles.
8. The polylysine conductive hydrogel according to claim 1, characterized in that: The photoinitiator described in step (3) includes at least one of I2959, LAP, and α-ketoglutaric acid.
9. The polylysine conductive hydrogel according to any one of claims 1 to 8 can be widely used in the fields of wound repair, cardiovascular, wearable devices and tissue engineering.
Citation Information
Patent Citations
Injectable hydrogel and preparation method thereof
CN110124117A
Conductive photo-thermal self-healing composite hydrogel dressing as well as preparation method and application thereof
CN111234267A
PH-responsive bi-crosslinking mussel bionic adhesion intelligent drug-loaded hydrogel as well as preparation method and application of pH-responsive bi-crosslinking mussel bionic adhesion intelligent drug-loaded hydrogel
CN112843327A